The Cybil war - Byars, Betsy Cromer; Owens, Gail. (New York : Viking Press, 1981)
Simon learns some hard lessons about good and bad friendships when his good friend Tony's stories involve him in some very troublesome and complicated situations.
Keywords: Friendship -- Fiction